Relationship Between Foreign Aid and Night Lights Data - Wan, Jean-Philippe (Université d'Ottawa | University of Ottawa, 2016)
This paper investigates the relationship between committed foreign aid and right light data from 1992 to 2008. Two aid data classifications were used: (i) humanitarian, early impact, late impact, and other aid and (ii) humanitarian and non humanitarian aid. The results show that the elasticity of our measure of night lights to humanitarian aid is negative and statistically significant at the 5% level for year 0 and 1 and statistically insignificant for year 2 onwards. The elasticities for early impact, late impact and non humanitarian aid are positive and statistically significant for year 1 and onwards. Foreign aid positively impact night light data and suggestively imply that foreign aid positively impact, albeit weakly economic activity. The heterogeneity of the results was investigated. The results were not sensitive to a change from non calibrated satellite images but did differ depending on the percentage electrification of a country, percentage of the total population that live in urban environments, and the initial level of prosperity of a country.